2012
DOI: 10.2298/hel1256119t
|View full text |Cite
|
Sign up to set email alerts
|

Vigor of sunflower and soybean aging seed

Abstract: Seed aging and deterioration affect seed vigor and viability. The characteristics of the chemical composition of oil crops seed are related to specific processes occurring in the seed during storage. This study was performed to examine the changes in seed vigor of different sunflower and soybean genotypes under controlled and conventional (uncontrolled) conditions of natural aging for six and twelve months. Obtained results show that the degree of seed damage and the ability of seed to resist the negative effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 12 publications
11
16
0
1
Order By: Relevance
“…Moreover, Gupta and Aneja [4] indicated that decreases in oil content between soybean cultivars may be due to age induced depletion phenomenon, improper storage environments and higher activity of storage fungi. These results are in good accordance with those obtained by Balesevic-Tubic, et al [7], Chuansin, et al [10], Erandes, et al [13] Jamro, et al [17] Khaliliaqdam, et al [19] Tatic, et al [30].…”
Section: Storage Cultivars Effectssupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, Gupta and Aneja [4] indicated that decreases in oil content between soybean cultivars may be due to age induced depletion phenomenon, improper storage environments and higher activity of storage fungi. These results are in good accordance with those obtained by Balesevic-Tubic, et al [7], Chuansin, et al [10], Erandes, et al [13] Jamro, et al [17] Khaliliaqdam, et al [19] Tatic, et al [30].…”
Section: Storage Cultivars Effectssupporting
confidence: 90%
“…Khaliliaqdamet, et al [19] suggested that variations occurred with the viability constants of a seed deterioration model between the soybean cultivars. Different periods of seed ageing, as well as storage conditions adversely affected the seed quality [30]. Similar inferences was reported by Sharma, et al [26], Simic, et al [29] and Vijay, et al [35].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…When seed could be packaged in moisture proof containers, the relative humidity of the air around the seed remains low, then the seed equilibrium moisture remains low (Poonam et al, 2001;Agha et al, 2004, Kong et al, 2008. Similar genetic variations in moisture content of soybean seed have also been reported by Tatic et al, 2012. These results are in good agreement with those reported by Tatipata (2009).…”
Section: Seed Moisture Content (Smc)supporting
confidence: 77%